THE ANALYSIS OF ILLOCUTIONARY ACT ON AUDIO FILE ENTITLED JAMA'AH AUSTRALIA - KEPENTINGAN MENGHIDUPKAN AMAL MASJID - Faisal Rusdianto (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2014)
The research design of this study is descriptive qualitative. The data sources of this study are audio file entitled Jama'ah Australia - Kepentingan Menghidupkan Amal Masjid which is taken from an interesting video uploaded by a member having the Youtube accountnamed Ummat Akhir Zaman a.k.a Syukri Abdullah. This interesting video is a record of English bayan (English Islamic sermon) given by the representative of Tablighi Jamaat member from Sydney, Australia. Even though it is in a form of video but there is no moving picture in itbut it is merely a one hour-five minutes and thirty one second MP3 recording file.This paper merely focuses on analyzing the most dominant types of Speech Acts on Audio File of Australian Jamaat English Islamic sermon entitled Jama'ah Australia - Kepentingan Menghidupkan AmalMasjid. This Audio File of Australian Jamaat English Islamic sermon is analyzed by the perspective of Searls theory. From the analysis of audio file entitled Jama'ah Australia - Kepentingan Menghidupkan Amal Masjid it can be found four types of Searles illocutionary acts: Directive, commisive, representative and expressive. There are 50 data of illocutionary acts which consist of : 8 data of the type of Directive: One data showing of stating and 7 data showing of suggesting, 4 data of the type of Commisive: Two data showing promising and 2 data showing of threatening, 36 data of the type of Representative: 5 data showing of asserting and 31 data showing of informing, and 2 data of the type of Expressive: 2 data showing the illocutionary acts of praising. From the classification of the data, it can be seen clearly that the type of commisive is the most dominant. This was used since the Australian speaker want toshow humbleness and politeness when he was giving sermon in front of Indonesian audience.